(untitled) (Jurnal Simki Economic, 2024)
Trade openness promotes industrialization and has a significant impact on a nation’s economic development. Increased economic growth can be a result of foreign investment, and state revenue can rise as a result of significant exports of domestic goods. This study aims to assess how economic trade openness affects the economic development of ASEAN nations. Cross-sectional and time-series analyses were conducted using panel data between 2013 and 2022. The study demonstrates that whereas FDI and positive and major economic growth, exports and positive and large economic growth, and imports and negative and insignificant economic growth, are all associated with significant inflation and negative economic growth. It is anticipated that the nation will raise the standard of goods to promote commerce and economic progress.